Competency in home body fat monitoring by portable devices based on bioelectrical impedance analysis: A pilot study - Himel Mondal; Shaikat Mondal; Chayan Baidya (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: With the advancement of bioelectrical impedance analysis method, body fat can be estimated with portable devices at home. These devices are popular in home body fat monitoring (HBFM). However, improper use of the device may provide erroneous result. AIM: This study aimed to find out the level of competency of the operator in HBFM. MATERIALS AND METHODS: A cross-sectional survey was conducted with 34 individuals (males = 11, females = 23) during March-December, 2017. A pretested questionnaire was used to collect information by expert interviewer. Data were collected about premeasurement precautions, steps followed in body fat measurement proper, and postmeasurement action. Survey data were expressed in mean, standard deviation, and percentage and statistically tested by unpaired t-test and Chi-square test according to necessity with α =0.05. Analyses were done in GraphPad Prism 6.01. RESULTS: Premeasurement precautions for maintaining proper hydration level were not followed by majority of the participants. Avoidance of exercise in preceding 12 h was not followed by 94.12% (χ2 = 26.47, P < 0.0001), voiding bladder before the measurement was not followed by 88.24% (χ2 = 19.88, P < 0.0001), and avoidance of diuretics (e.g., chocolate, caffeine) was not practiced by 82.35% (χ2 = 14.24, P = 0.0002). Prescribed steps for measurement proper were followed by majority of the operators. However, 61.76% (χ2 = 1.88, P = 0.17) forgot to keep log of the readings. CONCLUSION: Clinicians, fitness instructors, and nutritionists should emphasize on premeasurement factors for educating their clients for HBFM. This would help proper tracking of body fat level.